Pengembangan Bahan Ajar Leaflet Berbasis Kontekstual pada Pembelajaran IPA Kelas IV SD - Prandini Dianita Riski; Asep Sukenda Egok; Aswarliansyah Aswarliansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to develop a contextual based leaflet teaching material product for Class IV Sciene learning at SD Negeri 1 Sumber Harta in accordance with the 2013 curriculum and to produce leaflet teaching materials that are valid, practical, and have potential effects. This research is a development researh is a development reseach with a 4-D development model. The Four-D model consists of 4 stages, namely: the define stage, the design stage, the develop stage, and the disseminate stage. The subjects of this study were media experts, linguists, material experts, teachers, fourth grade students at SD Negeri 1 Sumber Harta with a total of 13 students. Data collection techniques using interviews, questionnaires, and test. The data analysis technique is based on the validation result of the validation analysis of media experts getting a score of 0.89, linguists getting a score of 0,83 and material experts getting a score of 0.83. based on the results of the analysis of the three validators, an average of 0.85 shows that contextual based leaflet teaching materials in science learning have met the valid criteria. Then the practicality analysis conducted by the teacher and students consisting of 6 people that contextually based leaflet teaching materials in science learning get an average score of 93.40% is categorized as very practical and has a potential effect of 92.30% which is categorized as very good. It can be concluded that centextually based leaflet teaching materials in science learning have met the criteria of being valid, practial, and have a potential effect so that they can be used in learning. Keywords: Leaflet Teaching Materials, Contextual, Science, SD